Causal association of circulating cytokines with sepsis: a Mendelian randomization study - Lin, Shan; Mao, Xueyan; He, Wanmei (Frontiers in Immunology, 2023)
Background: Observational studies have reported an association between circulating cytokines and sepsis. However, the precise causal relationship between these factors remains unclear. The objective of this study was to explore the causal link between circulating cytokines and sepsis using genetic data within the framework of Mendelian Randomization (MR).We performed a two-sample MR analysis to investigate this causality relationship in individuals of European ancestry. The publicly available genome-wide association studies (GWAS) statistics were used. We selected eligible instrumental single nucleotide polymorphisms (SNPs) that were significantly related to the circulating cytokines. Multiple MR analysis approaches were carried out, which included inverse variance weighted (IVW), Weighted Median, MR-Egger, Weighted Mode, Simple Mode, and MR pleiotropy residual sum and outlier (MR-PRESSO) methods.We found evidence to support the causal role of genetically predicted circulating levels on decreased risk of sepsis, including RANTES (OR = 0.920, 95% CI: 0.849-0.997, P = 0.041) and basic fibroblast growth factor (basic-FGF) (OR = 0.869, 95% CI: 0.766-0.986, P = 0.029). Additionally, MR analysis positive causal association of between beta-nerve growth factor (β-NGF) and sepsis (OR = 1.120, 95% CI: 1.037-1.211, P = 0.004). The results of MR-Egger, Weighted Median, Weighted Mode, and Simple Mode methods were consistent with the IVW estimates.Sensitivity analysis showed no horizontal pleiotropy to bias the causal estimates.This MR study provides first novel evidence that genetically predicted causal association of circulating levels of RANTES, basic-FGF, and β-NGF with altered sepsis risk. The findings shed light on the potential involvement of these cytokines in sepsis pathogenesis. Although requiring additional confirmation, the results contribute new insights into cytokine mediators in sepsis and suggest promising future research directions.